Theory of sets - Kamke, Erich, 1890-1961; Bagemihl, Frederick, 1920-2002 (New York (N.Y.) : Dover, 1950)
Clear and simple, this introduction to the theory of sets employs the discoveries of Cantor, Russell, Weierstrass, Zermelo, Bernstein, Dedekind, and other mathematicians. It analyzes concepts and principles, offering numerous examples. Starting with the rudiments of set theory, the text advances to arbitrary sets and their cardinal numbers, ordered sets and their order types, and well-ordered sets and their ordinal numbers. With its emphasis on fundamentals, the presentation is easily comprehensible to students acquainted with college-level algebra. 1950 ed.
Includes bibliographical references (p. 139) and index.
Keywords: Set theory